Beyond security, towards institution building: The case of NATO-Macedonia relations - Rainer Schweickert; Inna Melnykovska; Hanno Heitmann (Kiel Institute for the World Economy (IfW), 2012)
The effectiveness of NATO conditionality for institutional reforms is highly controversial. Some papers argue that any effect this conditionality might have had may be due to endogeneity effects, i.e. NATO may have picked the winners. We argue that this is not the case. First, NATO-Mazedonia relations provide a case in point. Macedonia was granted entry into the Membership Action Plan (MAP) in 1999 due to country's strategic importance. Only after the Ohrid agreement, effective conditionality set in and marked a switch in NATO strategy from security only towards institution building. Second, this is supported by econometric evidence based on panel data. An event study reveals that entry into NATO's accession process was mainly driven by neighbourhood and good relations with the West. We conclude that empirical evidence clearly supports a stronger role of NATO's political agenda, i.e., low entry barriers but strict accession conditionality.
Keywords: F52; F53; F59; 330; international organization; european integration; institutional development; accession incentives; regional security; Bündnissystem; Mitgliedschaft; Institutioneller Wandel; Mazedonien